In Between Centre and Periphery: Kenya as a Key Scientific Nation in East Africa? - Agnes Lutomiah; Jaco P. Blanckenberg; Stefan Skupien (Science, Technology and Society, 2022)
Kenya's government has identified science, technology and innovation as key for its national development plan and has started to refurbish its research environment. In this article, we use the world system approach to discuss the largely peripheral relations of Kenya's science systems to the global science system and to identify indications for Kenya becoming a semi-peripheral scientific player itself within Eastern Africa. While the publications are dominantly oriented towards the Global North and while foreign sources fund nearly half of Kenya's research and development (R&D), the country starts to become an important country for its neighbours. However, Kenya is still facing an unstable system of integrating significantly more graduate students. These are seen as essential to provide for a sustainable knowledge base that is required for the country's socio-economic goals. We point to the lack of robust and recent data on R&D in Kenya as an impediment to evidence-based policy-making.
Keywords: 300; science policy; research and development; PhD training; Kenya; centre-periphery